HPLC Method for Simultaneous Determination of Five Antiepileptic Drugs in Rat Plasma - Karami-Bonari, A.R.; Tamizi, E.; Samini, M.; Jabbaribar, F.; Jouyban, A. (Asian Journal of Chemistry, 2010)
A rapid, simple and sensitive method has been developed and validated for simultaneous determination of 5 antiepileptic drugs i.e., lamotrigine (LTG), oxcarbazepine (OXC), carbamazepine (CBZ), its major metabolite carbamazepine 10,11-epoxide (CBZE) and phenytoin (PHT) in plasma of rat by high-performance liquid chromatography (HPLC) with spectrophotometric detection. After protein precipitation with acetonitrile, separation is achieved on a Nova-Pak® C18 analytical column, using a ternary mixture of potassium dihydrogen phosphate buffer (pH 6.0)/acetonitrile/2-propanol (63:22:15, v/v/v) as the mobile phase, at a flow rate of 1.0 mL/min. The UV detector was set at 220 nm. The method was quantitatively evaluated in terms of linearity, accuracy, precision, limit of detection and limit of quantitation. which made it suitable for daily therapeutic drug monitoring.